2002
DOI: 10.1901/jeab.2002.77-29
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Functional Equivalence and Stimulus Equivalence: Effects of Baseline Reversals

Abstract: Functional equivalence and stimulus equivalence classes were established, reversed, and tested for stability with college students. Functional stimulus classes were established using a task in which students were trained to say nonsense words in the presence of arbitrarily assigned sets of symbols. Computer-controlled speech-recognition technology was used to record and analyze students' vocal responses for accuracy. After the establishment of stimulus classes was demonstrated with a transfer-of-function test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 26 publications
1
33
0
8
Order By: Relevance
“…Consideration of this issue may also provide some insights into performances during probe phases. Specifically, the current experimental preparations bear some functional similarity to preparations used to examine the effect of established functional classes on the emergence or reorganization of stimulus equivalence classes, and vice versa (e.g., Roche, Barnes, & Smeets, 1997;Tyndall, Roche, & James, 2004, Wirth & Chase, 2002. Such studies have generally found that incongruous relations between functional and stimulus equivalence classes lead to the delayed emergence or disruption of one or the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of this issue may also provide some insights into performances during probe phases. Specifically, the current experimental preparations bear some functional similarity to preparations used to examine the effect of established functional classes on the emergence or reorganization of stimulus equivalence classes, and vice versa (e.g., Roche, Barnes, & Smeets, 1997;Tyndall, Roche, & James, 2004, Wirth & Chase, 2002. Such studies have generally found that incongruous relations between functional and stimulus equivalence classes lead to the delayed emergence or disruption of one or the other.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is research evidence for this precise outcome. Specifically, Wirth and Chase (2002) found that the reversal of selected baseline simple discriminations used to disrupt two functional equivalence classes resulted in the complete reversal of response functions across both classes. They argued that this is to be expected because once functional equivalence among stimuli is established, any change in responding applied to one stimulus of a set must, by definition, be applied similarly to the other stimuli in the class.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be important to understand how to target or 'break-up' these maladaptive classes. Indeed, a number of researchers have examined whether or not established functional or stimulus equivalence classes can easily be reorganised (e.g., Dixon, Rehfeldt, Zlomke, & Robinson, 2006;Pilgrim, Chambers, & Galizio, 1995;Pilgrim & Galizio, 1990Smeets, Barnes-Holmes, Akpinar, & BarnesHolmes, 2003;Smeets, Barnes-Holmes, & Striefel, 2006;Wirth & Chase, 2002). Wilson and Hayes (1996) noted that two types of reversal training procedures have generally been employed in the empirical literature, complete reversal and partial reversal.…”
mentioning
confidence: 99%
“…Partial reversal is more commonly used which involves reversing only some of the trained relations and is usually less successful in reversing the established equivalence relations. While some suggestions have been made (e.g., as to the conditions under which established equivalence relations can be reorganised the general finding is that equivalence relations, once formed are difficult to change (e.g., Follette, 1998;Rehfeldt & Hayes, 2000;Wirth & Chase, 2002), with symmetry relations generally more sensitive to contingency reversals than symmetric transitivity (equivalence) relations (Smeets, et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation